2013
DOI: 10.1016/j.jpsychires.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive cognitive-behavioral therapy on cingulate neurochemistry in obsessive–compulsive disorder

Abstract: The neurophysiological bases of cognitive-behavioral therapy (CBT) for obsessive–compulsive disorder (OCD) are incompletely understood. Previous studies, though sparse, implicate metabolic changes in pregenual anterior cingulate cortex (pACC) and anterior middle cingulate cortex (aMCC) as neural correlates of response to CBT. The goal of this pilot study was to determine the relationship between levels of the neurochemically interlinked metabolites glutamate + glutamine (Glx) and N-acetyl-aspartate + N-acetyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 74 publications
4
30
0
1
Order By: Relevance
“…One study has shown the opposite, corticostriatal hypoconnectivity, in a group of unmedicated patients (Posner et al, 2014). In addition, altered anterior cingulate cortex metabolic activity has been observed in OCD on fluorodeoxyglucose-positron emission tomography and magnetic resonance spectroscopy (Perani et al, 1995;Ebert et al, 1997;Saxena et al, 2004Saxena et al, , 2009O'Neill et al, 2013). Taken together, these observations delineate a possible neuroanatomical substrate for OCD symptomatology.…”
Section: Introductionmentioning
confidence: 97%
“…One study has shown the opposite, corticostriatal hypoconnectivity, in a group of unmedicated patients (Posner et al, 2014). In addition, altered anterior cingulate cortex metabolic activity has been observed in OCD on fluorodeoxyglucose-positron emission tomography and magnetic resonance spectroscopy (Perani et al, 1995;Ebert et al, 1997;Saxena et al, 2004Saxena et al, , 2009O'Neill et al, 2013). Taken together, these observations delineate a possible neuroanatomical substrate for OCD symptomatology.…”
Section: Introductionmentioning
confidence: 97%
“…In future, it is expected that some biological factors may be integrated into risk assessment procedures, following the development of this knowledge base. For example, a reduced risk after treatment could be visualized with functional brain imaging, similar to an attempt to evaluate cognitive behavioral therapy using measurements of brain metabolism [80]. However, we should always be aware that risk assessment has substantive uncertainty and that risk management has historically been biased to the deprivation of human rights.…”
Section: Resultsmentioning
confidence: 99%
“…Em relação à concentração de glutamato no córtex cingulado medial anterior, observou-se redução em seus níveis após tratamento. Concentrações elevadas de NAA pré-tratamento apresentaram correlação com maiores índi-ces de melhora pós-tratamento (O'Neill et al, 2013). Já a concentração do metabólito (mio-) inositol no córtex orbito-frontal se mostrou fator preditor de boa resposta à TCC para o TOC.…”
Section: Evidências De Modifi Cações Neuroanatômicas E Funcionais No unclassified